FOREIGN DIRECT INVESTMENT IN ASEAN COUNTRIES, 1990-2012. - PADMANABHA RAMACHANDRA BHATT (Revista Galega de Economía, 2015)
The objectives of the paper are to study foreign trade and investment dimensions of ASEAN and to study the role of FDI to the growth of exports. Vector autoregression model (VAR) is adopted to estimate the long run causal relationship between exports, foreign direct investment and GDP. The cointegration test result shows that there exists a long run equilibrium relationship between exports, FDI and GDP. It is found from the estimated Error Correction Model that FDI is a significant variable and the result indicates that 1 unit increase in FDI in ASEAN will lead to 1.1 units increase in exports. Wald Test indicates that there is a bilateral relationship between Exports and FDI but unilateral relationship between FDI and GDP and the direction is from FDI to GDP which means that FDI causes GDP.